THE SIGNIFICANCE OF AKIDAH-AKHLAK. A COMPREHENSIVE LITERATURE REVIEW OF HAMKA’S PENUNTUN JIWA - Alexander Stark; Balazs Huszka; Yohan Kurniawan, (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2025)
In the analysis of Hamka’s literary work, the book Penuntun Jiwa is often neglected. Nonetheless, it constitutes a substantial contribution to the broader context of character development. In this article, the researchers try to position this small work within Hamka’s literary corpus. A phenomenological approach considered the lifeworld of Hamka. It was discovered that Hamka stressed that a person should learn how to be successful in this world and the hereafter. Many of his major works equip a person with a strong belief and good character. However, the book Penuntun Jiwa considers the influences of syaitan (Satan). Furthermore, Hamka's relocation to various places led to a transformation of his perspective. He could see the temptations that were a danger for the Muslim believer. Insofar the book Penuntun Jiwa could serve as a kind of guidebook due to its unique style, which combined ahadith and stories.